Can knowledge based treatment planning of VMAT for post-mastectomy locoregional radiotherapy involving internal mammary chain and supraclavicular fossa improve performance efficiency? - Phurailatpam, Reena; Sah, Muktar kumar; Wadasadawala, Tabassum; Khan, Asfiya; Palottukandy, Jithin; Gayake, Umesh; Jain, Jeevanshu; Sarin, Rajiv; Pathak, Rima; Krishnamurthy, Revathy; Joshi, Kishore; Swamidas, Jamema (Frontiers in Oncology, 2023)
AIM: To validate and evaluate the performance of knowledge-based treatment planning for Volumetric Modulated Arc Radiotherapy for post-mastectomy loco-regional radiotherapy. MATERIAL AND METHODS: Two knowledge-based planning (KBP) models for different dose prescriptions were built using the Eclipse RapidPlanTM v 16.1 (Varian Medical Systems, Palo Alto, USA) utilising the plans of previously treated patients with left-sided breast cancer who had undergone irradiation of the left chest wall, internal mammary nodal (IMN) region and supra-clavicular fossa (SCF). Plans of 60 and 73 patients were used to generate the KBP models for the prescriptions of 40 Gy in 15 fractions and 26 Gy in 5 fractions, respectively. Validation of the 26 Gy/5 fractions and 40 Gy/15 fractions KBP models was done in 13 and 10 patients, respectively. The clinical plans (CLI) and the KBP plans were compared on the basis of the conformation number, homogeneity index, conformity index, total monitoring units (MU), and various dosimetric parameters for the OARs and target volumes. Both the plans were checked for delivery accuracy by performing patient-specific delivery quality assurance. Statistical analysis of the two groups was done using the standard two-tailed paired t-test or Wilcoxon signed rank test, and p<0.05 was considered significant. An unbiased review of all the CLIs and KBP plans was done by two experienced radiation oncology consultants. RESULTS: A total of 20 metrics were compared. The KBPs were found to be either better (6/20 or comparable (10/20) to the CLIs for both the regimens. Plans were of similar quality as per the result of a unbiased review based on clinical goal, Dose volume histogram and the isodose wash slice by slice. An important gain was the reduction in the number of monitor units and complexity index in both the models, thereby improving the efficiency of treatment delivery. A dosimetric trade-off between lung and non-lung OARs was noticed with the use of KBP plans. CONCLUSION: KBP models for left-sided post-mastectomy loco-regional radiotherapy have been developed and validated for clinical use. Models for both the regimes were found to improve the efficiency of treatment delivery.